2008
DOI: 10.1677/jme-08-0063
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of multifocal papillary thyroid carcinoma

Abstract: Papillary thyroid carcinoma (PTC) frequently presents as a multifocal process. To study the importance of separating independent primary (IP) from intrathyroid metastatic (ITM) PTC, we examined 19 molecular markers on 42 separate tumors from 18 multifocal PTC cases. In 12 of 18 (66 . 7%) cases, including 6 of 12 (50%) papillary microcarcinoma cases, the same or similar profile of loss of heterozygosities (LOH) and v-raf murine sarcoma viral oncogene homolog B1 (BRAF) mutation was demonstrated, indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 51 publications
(52 reference statements)
5
48
3
Order By: Relevance
“…But other studies reported that there was no significant association between multifocality and LN metastasis or recurrence [17]. One explanation for this observation is that multifocality most often is the result of the development of multiple independent tumors and not a manifestation of intraglandular dissemination, as demonstrated by recent molecular investigations of multifocal PTC [17][18][19][20]. Each of the different microtumors seems to have the limited growth potential.…”
Section: Discussionmentioning
confidence: 99%
“…But other studies reported that there was no significant association between multifocality and LN metastasis or recurrence [17]. One explanation for this observation is that multifocality most often is the result of the development of multiple independent tumors and not a manifestation of intraglandular dissemination, as demonstrated by recent molecular investigations of multifocal PTC [17][18][19][20]. Each of the different microtumors seems to have the limited growth potential.…”
Section: Discussionmentioning
confidence: 99%
“…Follicular adenomas and Hürthle cell adenomas have similar gene expression profile as malignant tumors (Arora, Scognamiglio et al 2008). By detection of BRAF mutation and loss of heterozygosities (LOH), 66.7% papillary thyroid carcinomas (PTC), including 50% papillary microcarcinoma cases (<1 cm), were proved to be intrathyroid metastasis (Lin, Finkelstein et al 2008). Patients with intrathyroid metastasis, including papillary microcarcinoma, had significantly increased lymph node metastasis (Lin, Finkelstein et al 2008).…”
Section: Molecular Tests Used In Thyroid Nodular Lesionsmentioning
confidence: 99%
“…By detection of BRAF mutation and loss of heterozygosities (LOH), 66.7% papillary thyroid carcinomas (PTC), including 50% papillary microcarcinoma cases (<1 cm), were proved to be intrathyroid metastasis (Lin, Finkelstein et al 2008). Patients with intrathyroid metastasis, including papillary microcarcinoma, had significantly increased lymph node metastasis (Lin, Finkelstein et al 2008). LOHs of 17q21, 17p13, 10q23 and 22q13 may be important in predicting increased risk of lymph node metastasis (Lin, Finkelstein et al 2008).…”
Section: Molecular Tests Used In Thyroid Nodular Lesionsmentioning
confidence: 99%
See 2 more Smart Citations